AN ANALYSIS OF ILLOCUTIONARY ACTS BASED ON CONTEXTUAL ASPECT IN SHORT STORIES “FIVE GHOSTS“AND“BIRDS OF DIFFERENT FEATHERS” BY MADHU TANDON AND THITI TAVORA - Ani Yuliani Somantri (Journal of English Education Program (JEEP), 2015)
The study aims at analyzing speech acts particularly illocutionary acts based on contextual aspect particularly situational context in “Five Ghosts” and “Birds of Different Feathers” short stories written by Madhu Tandon and Thiti Tavora. Illocutionary act is the action that is performed by the utterances of what someone’s said. In this study, the researcher addressed two questions: 1). What kinds of Illocutionary act are found in contextual aspects of short stories entitled “Five Ghosts” and “Birds of Different Feathers”? 2). What kinds of illocutionary acts are most frequently appeared in contextual aspects of short story entitled “Five Ghosts” and “Birds of Different Feathers”?. To obtain the data, the researcher employed content analysis towards utterances in Five Ghost and Birds of Different Feathers short stories. The results revealed that utterances from 107 sentences, 50 utterances from Five Ghost short story and 57 utterances from Birds of Different Feathers. From the utterances of the first short story “Five Ghost” the writer found 17 sentences belong to directive (34%), 6 commissive (12%), 23 representative (46%) and 4 sentences belong to expressive (8%). Declarative was not found in this short story. Meanwhile from the utterances of the second short story ”Birds of Different Feathers” the writer found of 57 sentences, the writer found 20 sentences directive (35.08%), 16 representative (28.07%), expressive 15 (26.31%), declarative 1 (1.75%) and 5 sentences belong to commissive (8.77%). Kinds of illocutionary acts which most frequently  appeared  in the utterances Five Ghost short story based on Searle’s theory was dominated by Representative (46%), particularly asserting followed by expressive, commisive, assertive and there is no one belong to declarative. Meanwhile kinds of illocutionary acts which most frequently appeared in the utterances Birds of Different Feathers short story based on Searle’s theory was dominated by was dominated by Directive (35.08) particularly asking followed by expressive, commisive, assertive and declarative. Keywords: Illocutionary Acts, Utterances, Contextual aspect.